Diet composition of cobia fish, Rachycentron canadum (Linnaeus, 1766) from northeastern waters of Peninsular Malaysia - Zulhusni A.; Mazlan A.G.; Zaidi Che Cob; Samat A. (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study was conducted to investigate the food and feeding habits of cobia, Rachycentron canadum from the northeastern waters of Peninsular Malaysia. Stomach content of 82 R. canadum fish were analyzed with reference to gender and size classes. Fish was the most dominant diet component for R. canadum with % IRI value of 95.3%, followed by squid (3.1%), crab (1.5%), and shrimp (0.07%). Fish was also predominant regardless of gender and size classes of the R. canadum in the study area. Shrimp was not taken by the male, but found in females with sizes ranged between 80 and 120 cm TL. Rachycentron canadum that was larger than 120 cm TL also did not prefer crab as part of its diet component. Their feeding intensity increased with size accordingly that was indicated by the increase in the percentage of active feeder. This research finding will contribute to the development of R. canadum culture in Malaysia.